How and When Personal Initiative Helps University Students to Discover Entrepreneurial Opportunities: The Role of Risk-Taking and Creativity - Santos, S. C.; Junça Silva, A.; Duarte, H. (ESU, 2021)
The ability to discover entrepreneurial opportunities is a key competence to all university students. While students' personal initiative (Fay & Frese, 2001) drives work-related skills and attitudes, we do not know how and when it may be associated with entrepreneurial competencies. In this study, we address this gap by uncovering how and when student’s personal initiative leads to an increase in their ability to discover entrepreneurial opportunities. Specifically, we examine the role of risk-taking and creativity in the interplay between personal initiative and opportunity discovery competencies among university students. We propose that entrepreneurial risk-taking mediates the relationship between personal initiative and opportunity discovery competencies (Hypothesis 1). In addition, as creativity plays an important role in pursuing new business ideas, we anticipate that creativity moderates the positive effect of personal initiative on opportunity discovery via entrepreneurial risk-taking, such that the indirect positive effect is stronger for more creative students when compared to students with lower levels of creativity (Hypothesis 2). To test our hypotheses, we used a sample of 103 university undergraduate management students from Portugal. Students' average age is 20.39 years old (SD = 2.00), 57% are female. Most students do not consider entrepreneurship as a career choice after studies (75.7%), while 52.4% consider it a career choice 5 years after studies. Data collection was developed in two time moments. Specifically, personal initiative and entrepreneurial risk-taking were measured in time 1, and creativity and opportunity discovery abilities were measured two months later. Data analysis followed a two-step process: first, we tested the simple mediation model, and next we analyzed the proposed moderation effect and the second-stage moderated mediation (Hayes, 2015, 2018). We used the PROCESS macro for SPSS (v3.4), bootstrapping 5000 samples to obtain 95% bias-corrected confidence intervals (BCs CIs) for all model estimations. Hypothesis 1 predicted that entrepreneurial risk-taking would mediate the link between personal initiative and opportunity discovery. Results showed no significant direct effect between personal initiative and opportunity discovery (B=0.12, p=0.17.). Yet, this non-significant relationship turns statistically significant and positive when entrepreneurial risk-taking is introduced in the regression model (Indirect effect=0.15), supporting hypothesis 1. Bootstrap analyses also show that this indirect effect is significant (95% BC CIs [0.03; 0.28]). Hypothesis 2 proposed that creativity would moderate the mediation effect of entrepreneurial risk-taking in the relationship between personal initiative and opportunity discovery. The interaction effect between entrepreneurial risk-taking and creativity on opportunity discovery is significant and positive (coeff=0.16, p<0.05). Looking closer at the direct conditional effects, we found that the relationship between entrepreneurial risk-taking and opportunity discovery is positive and statistically significant when students display average or above the average (+1 S.D.) creativity, being the relationship significantly stronger when the individual has creativity above the average (1 SD above the mean; b=0.72, p < 0.001), when compared to lower levels of creativity (1 SD below the mean; b=0.05, n.s.). The indirect effect of the personal initiative on opportunity discovery through entrepreneurial risk-taking seems to increase when the student’s creativity increases, as the index of moderated mediation is positive (Index=0.09; 95% CI [0.01; 0.18]). As the confidence interval does not include zero, and with the upper bound positive, the conclusion is that the indirect effect of personal initiative on opportunity discovery through entrepreneurial risk-taking is positively moderated by creativity. More specifically, the conditional indirect effects show that the indirect effect of personal initiative on opportunity discovery through entrepreneurial risk-taking is significantly stronger when the individual has above the average creativity abilities (1 SD above the mean; b=0.16, 95% CI [0.04 ; 0.28]), when compared to average or below the average creativity (1 SD below the mean; b=0.03, 95% CI [-0.08 ; 0.14]; Average b=0.10, 95% CI [-0.01 ; 0.19]. These results support hypothesis 2. We conclude by discussing the implications of our results on entrepreneurship education and how to develop opportunity discovery competencies among students.